2019
DOI: 10.1111/nhs.12601
|View full text |Cite
|
Sign up to set email alerts
|

Skill mix change between physicians, nurse practitioners, physician assistants, and nurses in nursing homes: A qualitative study

Abstract: Nursing home physicians face heavy workloads, because of the aging population and rising number of older adults with one or more chronic diseases. Skill mix change, in which professionals perform tasks previously reserved for physicians independently or under supervision, could be an answer to this challenge. The aim of this study was to describe how skill mix change in nursing homes is organized from four monodisciplinary perspectives and the interdisciplinary perspective, what influences it, and what its eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 31 publications
(42 reference statements)
1
27
0
2
Order By: Relevance
“…A systematic review showed that substituting nursing home physicians with NPs, PAs or RNs appears to achieve at least as good resident and process of care outcomes as care provided by physicians 14. In a focus group study with professionals in Dutch nursing homes, the contributions of NPs, PAs and RNs to quality healthcare, provision of resident-centred care and strengthening of the care team was considered an added value 15. Nevertheless, the same study showed that physician substitution was organised by different professionals (NPs, PAs, RNs) with different tasks and responsibilities, and there was no consensus on optimal organisation.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review showed that substituting nursing home physicians with NPs, PAs or RNs appears to achieve at least as good resident and process of care outcomes as care provided by physicians 14. In a focus group study with professionals in Dutch nursing homes, the contributions of NPs, PAs and RNs to quality healthcare, provision of resident-centred care and strengthening of the care team was considered an added value 15. Nevertheless, the same study showed that physician substitution was organised by different professionals (NPs, PAs, RNs) with different tasks and responsibilities, and there was no consensus on optimal organisation.…”
Section: Introductionmentioning
confidence: 99%
“…These sources have pointed out that the actual manifestation of task shifting is broader than non-medical prescribing, and that more (diverse) opportunities of task shifting should be recognised. 17,18 Examples of opportunities that may increase the quality of care include a proactive role for pharmacists in drug management within general practices or the expanding role for technology in ophthalmology. In particular, task shifting as a way to achieve the right skill-mix of a team of professionals responsible for the care of a specific group of patients is vital.…”
Section: The Diversity Of Task Shifting In Practicementioning
confidence: 99%
“…Olandijoje atliktuose tyrimuose buvo nustatyta, kad priežiūros kokybės gerinimas ir galimybė siūlyti papildomas paslaugas bei geresnis pacientų priežiūros tęstinumas buvo svarbūs veiksniai, paskatinę integruoti IPS į šeimos gydytojo komandą [25,26].…”
Section: Tyrimo Medžiaga Ir Metodaiunclassified